Pengaruh Pembiayaan Cicil Emas, Mitraguna, dan BSI Griya Hasanah Terhadap ROA Pada BSI Kc Makassar 2 Dengan Islamic Branding Sebagai Variabel Intervening - Ahsana, Hardiyanti Ade; Siradjuddin, Siradjuddin; Haddade, Abdul Wahid (LPPM Institut Pendidikan Nusantara Global, 2024)
The aims of the study were to discover the effect: 1) Knowing the effect of gold installment financing on ROA; 2) Knowing the effect of partner financing on ROA; 3) Knowing the effect of BSI Griya Hasanah financing on ROA; 4) Knowing the influence of Islamic Branding on ROA; 5) Knowing the effect of gold installment financing through Islamic Branding on ROA; 6) Knowing the effect of partner financing through Islamic Branding on ROA; and 7) Knowing the effect of BSI Griya Hasanah financing through Islamic Branding on ROA at Bank Syariah Indonesia KC Makassar 2. This research is quantitative research with an associative approach. The data sources are primary data from questionnaires and secondary data from the financial reports of PT Bank Syariah Indonesia Makassar Branch Office 2. Data collection methods are observation, interviews, literature studies, and questionnaires with a Likert scale. The results of the study indicate that: 1) gold installment financing has a positive and insignificant effect on Return on Assets (ROA); 2) Partner financing has a positive and insignificant effect on Return on Assets (ROA); 3) BSI Griya Hasanah financing has a positive and significant effect on Return on Assets (ROA); 4) Islamic Branding has a positive and significant influence on Return on Assets (ROA); 5) Gold installment financing has a positive and insignificant effect on Return on Assets (ROA) through Islamic Branding; 6) Partner financing has a positive and insignificant effect on Return on Assets (ROA) through Islamic Branding; and 7) BSI griya Hasanah financing has a positive and significant effect on Return on Assets (ROA) through Islamic Branding at Bank Syariah Indonesia KC Makassar 2.